PenerapanMetode Support Vector Machine (SVM) Guna Menentukan Tingkat Lulus Mahasiswa E-Learning - Firmansyah Firmansyah (LPPM STMIK ANTAR BANGSA, 2017)
Abstractâ€”Elearning system is a web -based communication platform that enables learners , without limitation of place and time , to access a variety of learning tools such as discussion forums , assessment , content repositories , and document sharing system . E -Learning can be just as effective as face-to- face in a conventional classroom teaching and learning , if proper teaching techniques and well-organized ( Oztekin et al . 2013 ) . Based on the data processing has been done with membandingakan algorithm and Support Vector Machine Support Vector Machine by using the log data of students . Later in the test to get the accuracy and AUC values of each algorithm so that the highest test results obtained by using support vector machine an accuracy of 81.02%, and AUC value of 0.810 .Â Intisari-E-Learning adalahsistemwebplatform komunikasiberbasisyang memungkinkanpeserta didik, tanpa batasantempatdan waktu, untuk mengaksesberbagai alatbelajar, sepertiforum diskusi, penilaian, repositorikonten, dansistemsharing dokumen. E-Learning bisa samaefektifnya dengantatap mukadalampengajaran di kelaskonvensional danbelajar, jikateknik mengajaryang tepatdanterorganisir dengan baik(Oztekin et al.2013). Berdasarkanpengolahan datayang telah dilakukandenganalgoritmamembandingkandanSupport VectorMachineSupport VectorMachinedengan menggunakandatalogdarisiswa.Kemudian ditesuntuk mendapatkanakurasidan nilai-nilaiAUCsetiapalgoritmasehinggahasil tesyang tertinggidiperoleh dengan menggunakanmesindukunganvektordengan akurasi 81.02%, dan nilaiAUC0.810